Robiya SOURCES OF FORMATION OF LEGAL TERMS: SOURCES OF FORMATION OF LEGAL TERMS - G'afurova, Robiya (Журнал иностранных языков и лингвистики, 2022)
Legal Terminology has a significant place in the terminological system of any language, as legal terminology is the determining factor research and improvement of legal knowledge in various social directions of society.